A Matrix Approach for Divisibility Properties of the Generalized Fibonacci Sequence - Aynur Yalçiner (Discrete Dynamics in Nature and Society)
We give divisibility properties of the generalized Fibonacci sequence by matrix methods. We also present new recursive identities for the generalized Fibonacci and Lucas sequences.